Meningkatkan Daya Tarik Pembeli pada Ampera Bintang Mulia - Dhini Rahmawati; Janeza Revel; Putri Dwi Julita; Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
The influence of current technology can change the marketing strategies of all business people. Where the right business strategy in this advanced era will advance the business. This encourages business people to implement innovative marketing strategies, especially through online media. This article provides information regarding the design and implementation of websites for businesses that offer daily food. In this project, we chose the Blogger platform as the main development tool for creating a website. Several stages of creating a website are data collection, system analysis, website design using the blogger platform. This project aims to increase product exposure, expand market reach, and improve product marketing and promotion processes. It is hoped that this project will benefit Ampera Bintang Mulia by increasing the number of customers.